Exploring Physiology and Body Traits of Finswimming Athletes and Trained Swimmers - Dadan Resmana; Sendy Mohamad Anugrah; Raisa Ganeswara (Universitas Pendidikan Indonesia, 2024)
In practical situations, athletes often face certain limitations in the transition to finswimming. Consequently, coaching procedures focus on the conversion of trained-swimmers into finswimming athletes. This study aimed to conduct a comparative analysis of the anthropometric characteristics, aerobic capacity, and respiratory capacity of athletes engaged in finswimming and those trained in traditional swimming. Fifteen male finswimming athletes and trained-swimmers aged 18-19 years participated in the study. They performed a progressive maximal treadmill test under laboratory conditions for measuring their aerobic capacities. Respiratory capacity was measured using spirometer, while body fat percentage was measured using GE Lunar Prodigy DXA. The result showed that the finswimming athletes had statistically higher values of aerobic capacity and respiratory capacity compared to trained-swimmers. Meanwhile, trained-swimmers had statistically higher values of body fat percentage compared to finswimming athletes. Based on these findings, we conclude that finswimmers exhibit a pronounced advantage in aerobic capacity, body fat, and respiratory capacity. While certain parameters, notably respiratory and aerobic capacities, demonstrated marked disparities between the two cohorts, other elements showcased a parallel nature. This conveys the potential for trained swimmers, as identified in this study, to ascend to the levels of athletes by adopting analogous structured training schedules and nutritional regimes akin to those observed in finswimmers.